White light emission from AIE‐active luminescent organic materials. Issue 5 (23rd March 2022) - Kumari, Beena; Dahiwadkar, Rahul; Kanvah, Sriram
Abstract: Fluorescent organic materials that exhibit unique aggregation‐induced emission have been utilized for various applications, including white light emission (WLE). The materials typically rely on composite designs involving a mixture of compounds emitting at different wavelengths of light. To overcome the limitations offered by the design of such composite mixtures, tremendous efforts were also emphasized in developing single‐molecule substrates that emit white light. The white light by either method is typically controlled by the solvent polarity, energy and charge transfer, host‐guest interactions, gelation, or embedding in the polymer or organic frameworks. This article briefly reviews various molecules exhibiting aggregation‐induced emission behavior and emitting white light. Abstract : This article comprehensively captures various AIE‐active organic materials and their versatile designs to achieve white light emission. The strategies include color complementary luminescent mixtures to single‐molecule fluorescent or phosphorescent emitters in solution and solid state.